Protein Kinase C Protocols - Newton, Alexandra C.; Newton, Alexandra C. (Methods in Molecular Biology,, 2003)
Protein kinase C impacts on nearly every aspect of signal transduction, placing it at the forefront of research in how cells transduce information. In Protein Kinase C Protocols, leading investigators from academia and industry present a comprehensive collection of classical and emerging laboratory techniques for the study of this influential protein, all optimized for successful and reproducible results. Described in step-by-step detail, these methods can be easily used to explore the structure, function, regulation, subcellular localization, and macromolecular interactions of protein kinase C. Included in this collection are easy-to-follow techniques to purify protein kinase C, to measure its activity and its membrane interaction in vivo and in vitro, and to identify substrates. There are also methodologies and techniques for measuring the phosphorylation state of protein kinase C, for expressing and analyzing the membrane-targeting domains of protein kinase C, and for detecting binding proteins. Additional chapters address pharmacological probes, genetic approaches, and protein kinase C in disease. Each protocol is introduced in the context of protein kinase C function and regulation and contains many notes on how best to deal with the problems that may occur. Comprehensive and authoritative, Protein Kinase C Protocols offers a timely compilation of biophysical, biochemical, cell biological, and molecular biological approaches that will ensure successful results in every laboratory working in this rapidly advancing field.